An integrated energy system scheduling optimization method considering economy, stability and environmental protection. Issue 1 (May 2021) - Lou, Qinghui; Chen, Jun; Niu, Honghai; Qiu, Rui; Wu, Jun; Gao, Yuan; Ma, Xiangzhui; Guan, Xiaocheng; Ouyang, Jun
Abstract: In this paper, first, an energy efficiency evaluation method including economy, stability and environmental protection was given. Second, a mathematical model of the integrated energy system and a single-objective economic optimization model under different operation conditions, which add renewable energy and power storage equipment and could be solved based on the greedy algorithm, were given to improve the energy efficiency. Finally, an integrated energy system including wind power, photovoltaics, power storage equipment and conventional loads was taken as an example. Considering the time-of-use electricity price and the full utilization of energy storage, 4 optimization plans were set up for comprehensive energy efficiency evaluation and comparison. The result shows that the energy efficiency evaluation method proposed in this paper is practical and feasible, and the optimization method proposed plays a guiding role in the operation of similar parks.